EVALUASI MANAJEMEN PENGELOLAAN LIMBAH MEDIS PADAT INFEKSIUS DI RUMAH SAKIT UMUM DELI SERDANG KECAMATAN LUBUK PAKAM KABUPATEN DELI SERDANG - WAHYU WIDIARTI; ERLEDIS SIMANJUNTAK; MIDO ESTER SITORUS (LP2MTBM MAKARIOZ, 2019)
Infectious solid medical waste is one type of hazardous waste because it can potentially infect others. Therefore, waste management must be in accordance with regulations. This study aims to determine the evaluation of management of infectious solid medical waste management in Deli Serdang General Hospital, Lubuk Pakam District, Deli Serdang Regency. This research is a qualitative research with an exploratory descriptive approach which is a research method that aims to obtain a description of a situation objectively. The study was conducted at Deli Serdang General Hospital in June 2019. Researcher used questionnaires, observation guides, and documentation in collecting data. 6 (six) informants, namely the head of the secretariat, the head of the environmental health installation and the person in charge of the incinerator, the head of the general subdivision, the incinerator staff of 2 people, and the head of clinical pathology. Data analysis was performed using triangulation of descriptive data. The results showed that the planning and supervision phases were going well, but the organizing and implementation phases had not been carried out properly. Officers do not use complete Personal Protective Equipment, waste buildup occurs in temporary storage, and final treatment has not been carried out in accordance with applicable regulations due to the unavailability of fuel and water machines that are damaged. The results of infectious solid medical waste discharges haven’t met environmental quality standard because the parameter values of emissions are overthe maximum level. It is expected that hospitals will conduct special training on the management of infectious solid medical waste for officers so that officers can carry out their responsibilities in accordance with established regulations.